2017
DOI: 10.1007/s12560-017-9324-2
|View full text |Cite
|
Sign up to set email alerts
|

Virological Quality of Irrigation Water Sources and Pepper Mild Mottle Virus and Tobacco Mosaic Virus as Index of Pathogenic Virus Contamination Level

Abstract: Irrigation water is a doorway for the pathogen contamination of fresh produce. We quantified pathogenic viruses [human adenoviruses, noroviruses of genogroups I and II, group A rotaviruses, Aichi virus 1 (AiV-1), enteroviruses (EnVs), and salivirus (SaliV)] and examined potential index viruses [JC and BK polyomaviruses (JCPyVs and BKPyVs), pepper mild mottle virus (PMMoV), and tobacco mosaic virus (TMV)] in irrigation water sources in the Kathmandu Valley, Nepal. River, sewage, wastewater treatment plant (WWTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 57 publications
3
51
0
Order By: Relevance
“…Occurrence. PMMoV has been detected in aquatic environments around the world, including rivers, 28,32 aquifers, 41 irrigation, 32,42 and coastal and marine waters ( Fig. 1, Table 2).…”
Section: Freshwater Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Occurrence. PMMoV has been detected in aquatic environments around the world, including rivers, 28,32 aquifers, 41 irrigation, 32,42 and coastal and marine waters ( Fig. 1, Table 2).…”
Section: Freshwater Environmentsmentioning
confidence: 99%
“…In irrigation waters, 3/3 (100%) samples were positive for PMMoV; however, only one sample had a quantifiable concentration of 1.0 × 10 4 GC/ L. 32 Another study in 2017 looked at irrigation waters from the Kathmandu Valley from a variety of sources used for irrigating fresh produce. 42 Thirty-five surface water and six groundwater samples were collected. Sampling sites included six rivers, two ponds, one canal, and six groundwater wells.…”
Section: Freshwater Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies successfully demonstrated that several types of viruses, such as human adenoviruses (HuAdVs), polyomaviruses, enteroviruses (EVs), Aichi virus 1 (AiV-1), and pepper mild mottle virus (PMMoV), can be used as potential indicators to illustrate the adequate reduction of viruses in wastewater [13][14][15] . Studies showed that PMMoV and tobacco mosaic virus (TMV) are the most abundant and frequently detected viruses in sewage [15][16][17] . They are distributed globally and more abundant in environmental samples than human entric viruses, without any pronounced seasonal variation 18,19 .…”
mentioning
confidence: 99%
“…Reads of the tobacco mosaic virus and cucumber mosaic virus were found in most of the samples except negative control and the samples collected from biosafety cabinets in BSL-II (H1 and H4). As reported, the two kinds of viruses are widely distributed in water and soil [33,34]. The hepatitis C virus and rotavirus, not used in the lab, were found in samples from the centrifuge rotor (H6) and the bench in BSL-I with less than ten reads.…”
Section: Discussionmentioning
confidence: 93%